(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article is devoted to the field of theolinguistics, which investigates the interrelationship between religion and language. Theolinguistics analyzes religious texts, religious terminology, and the linguistic representation of religious meanings. The article presents the historical development of this field, its core directions, and the state of theolinguistic studies in Uzbekistan. It highlights critical aspects such as sacred texts, the specialized language used in religious discourse and worship, and the influence of religion on language. Although theolinguistics is a relatively new area of study in Uzbekistan, increasing interest in religious and linguistic issues enhances its prospects for further development. The article also reflects on the importance and future directions of theolinguistic research.